2017
DOI: 10.1063/1.4993941
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of resonance formation in microhydrated molecules. I. Pyridine-(H2O)n, n = 1,2,3,5

Abstract: We present R-matrix calculations for electron scattering from microhydrated pyridine. We studied the pyridine-HO cluster at static-exchange (SE), SE + polarization, and close-coupling levels, and pyridine-(HO) n = 2, 3, and 5 at SE level only in order to investigate the effect of hydrogen bonding on the resonances of pyridine. We analyse the results in terms of direct and indirect effects. We observe that the total (direct plus indirect) effect of microhydration leads to the stabilization of all resonances stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
3
19
1
Order By: Relevance
“…Although both our [34] and the earlier SMC calculations performed both at SE and SEP level showed that similar conclusions were reached for both types of calculations, inclusion of the polarization effects in a consistent way should provide a more accurate picture and improve our understanding of microhydration effects.…”
Section: Effect Of Microhydrationsupporting
confidence: 79%
See 3 more Smart Citations
“…Although both our [34] and the earlier SMC calculations performed both at SE and SEP level showed that similar conclusions were reached for both types of calculations, inclusion of the polarization effects in a consistent way should provide a more accurate picture and improve our understanding of microhydration effects.…”
Section: Effect Of Microhydrationsupporting
confidence: 79%
“…Using the R-matrix method and the UKRmol+ suite, extensive studies of pyridine-(H 2 O) n and thymine-(H 2 O) n with n=1, 2, 3, 5 were performed [34,35] at the SE level in order to understand the effect of microhydration on the two lowest π * shape resonances present in both ring molecules (see, for example, [36,37]). Earlier studies [38] using the Schwinger multichannel method (SMC) for the π * shape resonance of formic acid in clusters with 1 and 2 water molecules showed that: (i) the effect of water on the resonance position depended on whether H 2 O was the hydrogen donor/acceptor in the hydrogen bond, with the former leading to a lowering of the resonance energy and the latter to an increase; (ii) the effect was qualitatively additive.…”
Section: Effect Of Microhydrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The suite is able to model electronic excitation for small and mid-size molecules very accurately as well as describe their coreexcited resonances [71,72]. Among the largest targets studied (in terms of number of atoms in the system) are the molecular clusters pyridine-(H 2 O) 5 and thymine-(H 2 O) 5 for which SE and SEP calculations have been performed [42,43].…”
Section: Ukrmol-outmentioning
confidence: 99%